Phytochemical constituents and pharmacological activities of Lagerstroemia floribunda Jack. (Kedah bungor): A Review - Mukesh S. Sikarwar, Lee Chee Chung, Lo Wei Ting, Lim Chuan Chee, Shivkanya Fuloria, Kaveti Balaji (Journal of Applied Pharmaceutical Science, 2016)
This is the first report on review of Lagerstroemia species which includes the detailed description on phytochemistry and its pharmacological research. Despite being rich in important phytochemicals and having possible medicinal value there is no enough information available on this plant. Lagerstroemia floribunda Jack also known as Thai crape myrtle and kedah bungor, is a species of flowering plant in the Lythraceae family. This delightful ornamental plant is native to subtropical and tropical South-East Asia, from southern China to Myanmar, Thailand, Cambodia, Indo-China and Peninsular Malaysia. The phytoconstituents of Lagerstroemia floribunda includes 23-hydroxyursoIic acid, alphitolic acid, ursolic acid, dihydro-β-cyclopyrethrosin, sesamin, β -sitosterol, clauslactone-K, betulinic acid, lingueresinol, ent-isolariciresinol. Some of the researches that are being carried out on this plant include total phenolic contents and antioxidative activity of its flowers. This review will help to provide detailed information on recent researches done on this plant.
Keywords: Lagerstroemia floribunda,kedah bungor,phytochemistry.